2003
DOI: 10.1023/b:bebm.0000010967.24302.78
|View full text |Cite
|
Sign up to set email alerts
|

OXYS Rats as a Model of Senile Cataract

Abstract: Changes in the lens appear by the age of 2 months in early aging OXYS rats, at the age of 6 months these changes are detected in 100% animals, and by 12 months both eyes are involved. According to biomicroscopy findings, predominant forms of cataract are vesicular, annular, and dendritic, located in the cortical layer and/or nucleus of the lens. Light and electron microscopy showed morphological changes involving all structural components of the lens: epithelial degeneration progressing with age, deformation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…These mechanisms may also have to do with the reduced level of oxidative damage in tissues and organs. Previously we showed that agerelated accumulation of the lipid and protein oxidation levels were abolished by adding to the food of SkQ1 in the same as in the present study, a dose in tissues of Wistar and more significantly of OXYS rats [23].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These mechanisms may also have to do with the reduced level of oxidative damage in tissues and organs. Previously we showed that agerelated accumulation of the lipid and protein oxidation levels were abolished by adding to the food of SkQ1 in the same as in the present study, a dose in tissues of Wistar and more significantly of OXYS rats [23].…”
Section: Discussionsupporting
confidence: 82%
“…In comparison, for MitoQ this value is less than 2 times [22]. According to our data, addition of the above-mentioned SkQ1 amounts to the food completely prevents development of cataract and retinopathy in OXYS rats [23,24] as well as the age-dependent decline of the immune system [25,26].…”
Section: Introductionmentioning
confidence: 45%
“…The selection of this strain was initiated by R. I. Salganik at the Novosibirsk Institute of Cytology and Genetics [45]. A few months after birth, such age-related diseases as cataract and retinal dystrophy appeared in these animals [46][47][48]. N. G. Kolosova and colleagues in the same institute found that the development of these signs of aging was strongly decelerated by treatment with SkQ1 (50-250 nmol/kg per day with food).…”
Section: The First Results Of the Project: Skqs As Tools Against Oxidmentioning
confidence: 99%
“…The OXYS strain of rats may be very useful as a model to study the role of ROS in the process of aging, since this strain is characterized by ROS overproduction or by increased sensitivity to free radicals, which forms the basis of premature aging, short lifespan, low fertility, and increased frequency of cancers and chronic diseases (cataracts, cardiomyopathy, etc.) [13,14,29,30].…”
Section: Discussionmentioning
confidence: 99%